2021
DOI: 10.4103/gmit.gmit_78_20
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Proteome Profile of Women during Fertile Phase of Menstrual Cycle as Characterized by Mass Spectrometry

Abstract: Objectives: Ovulation is such a critical physiological process that its noninvasive detection based on salivary constituents has several advantages in humans. Hence, the present study is proposed to identify the ovulatory-specific proteins in saliva in order to detect ovulation phase. Materials and Methods: Samples were collected from women volunteers. The procedure adopted was approved by the Institutional Human Ethical Committee (DM/2014/101/38), Bharathidasan Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Human saliva contains several Cystatin family proteins, including Cystatin-A, Cystatin-B, Cystatin-C, Cystatin-D, Cystatin-S, Cystatin-SA and Cystatin-SN 63 . Particularly appearance of Cystatin-S, a cysteine protease inhibitor, is prominent during the ovulatory phase 28 . However, in the present study, Cystatin-A appeared during REP condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human saliva contains several Cystatin family proteins, including Cystatin-A, Cystatin-B, Cystatin-C, Cystatin-D, Cystatin-S, Cystatin-SA and Cystatin-SN 63 . Particularly appearance of Cystatin-S, a cysteine protease inhibitor, is prominent during the ovulatory phase 28 . However, in the present study, Cystatin-A appeared during REP condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, salivary proteins have been recommended as biomarkers to predict disease conditions such as Sjogren’s syndrome 19 , lung cancer 20 , oral cancer 21 , several systemic diseases 22 , HIV infection 23 , 24 , dental pellicle development 25 , hyperglycemia 26 , etc. Recently, it has been reported that salivary hormones and proteins have the potential to predict ovulation in women 27 , 28 . Saliva offers advantages such as easy non-invasive sampling, potential for large-scale studies, and the development of point-of-care platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Some weaker but still promising candidates include serine protease inhibitor E2 (SERPINE2), which has been correlated with oocyte maturity and successful fertilization ( 214 ), and Cystatin S, isoforms of which were found to be heavily isolated to ovulatory vs. pre- or post-ovulatory phases ( 215 , 216 ).…”
Section: Promising New Molecular Biomarkers To Predict Rtfmentioning
confidence: 99%